The Gut Bacteria of Gampsocleis gratiosa (Orthoptera: Tettigoniidae) by Culturomics - Hongmei Li; Huimin Huang; Ying Jia; Yuwei Tong; Zhijun Zhou (Insects)
Gampsocleis gratiosa Brunner von Wattenwyl, 1862, is a type of omnivorous chirping insect with a long history of artificial breeding. It has high economic value and is also an excellent orthopteran model organism. In this study, 12 types of culture media combined with 16S rRNA sequencing were employed to isolate 838 bacterial strains from the gut of G. gratiosa. After sequence comparison, a total of 98 species of bacteria were identified, belonging to 3 phyla, 5 classes, 11 orders, 20 families, and 45 genera. Firmicutes and Proteobacteria accounted for the majority (92.86%). At the order level, Enterobacteriaceae, Bacillales, and Lactobacillales predominated (79.59%). At the genus level, Klebsiella (11.22%) and Enterococcus (7.14%) predominated. This study also enumerated the strain morphological, physiological and biochemical properties of 98 species of bacteria, including colony morphology, Gram staining, bacterial motility test, temperature gradient growth, pH gradient growth, citrate utilization test, temperature oxidase test, contact enzyme test, methyl red test, V-P test, indole test, gelatin liquefaction test, nitrate reduction test, hydrogen sulfide test, starch hydrolysis test, cellulose decomposition test, esterase (corn oil) test and antibiotic susceptibility testing. Additionally, 16 antibiotics were utilized to test the bacterial susceptibility of the strains. This study explored the types and community structure of some culturable microorganisms in the intestinal tract of G. gratiosa and recorded their physiological characteristics. These data reflect the physiological functions of the intestinal microorganisms of G. gratiosa and provide support for subsequent research on the interaction mechanism between microorganisms and their hosts.